Finite difference solution on non-staggered grid for laminar flow through square-edged office - Dagtekin, I; Öztop, Hakan Fehmi; Eren, H (Begell House, Inc, 1999)
In this study, the incompressible two dimensional Navier-Stokes equations for laminar now through square-edged orifice were solved by an explicit formulation on non-staggered grid using SIMPLEM algorithm. The effects of orifice plate thickness (t*), orifice plate ratio (beta) and Reynolds number on now characteristics have been investigated numerically. The separated Row regions, pressure distribution, velocity profiles, discharge coefficients, vortex formations, and the streamlines patterns have been obtained and compared with results in the literature.
2nd Trabzon International Energy and Environment Symposium -- JUL 26-29, 1998 -- KARADENIZ TECH UNIV, TRABZON, TURKEY